ECONOMIC SIGNIFICANCE, NUTRITIONAL VALUE AND APPLICATION OF TRITICALE - Babić, Violeta; Rajičić, Vera Radomir; Đurić, Nenad (Economics of Agriculture, 2021)
Triticale is a new type of real grain, which was created by the breeding and selection of a man. This species deserves more and more attention from both domestic producers and producers on a global scale because it encompassed all the positive properties of wheat and rye. The paper clearly presents the knowledge about the importance, nutritional value and application of triticale and the effect of its usage in a diet of monogastric animals. The variety of uses, appropriate chemical composition, acceptable and studied breeding technology, classifies triticale as an irreplaceable source of energy and protein needs of animals. Due to its multiple usages: for grain, fodder and as a raw material for biofuel, contributes to the economic sustainability of crop production. The needs of this plant at the level of agrotechnical investments are less than in other cereals, so triticale is increasingly presented in organic and sustainable agricultural production.